FitFlame – Health and Fitness Coaching Application to Mitigate the Issues in the Current Applications - G. P. R. Lakshith; M. W. A. N. C. Muthukumarana; H. A. N. S. Perera; K. G. P. C. Kariyawasam; D. I. De Silva; R. R. P. De Zoysa (International Journal of Engineering and Management Research, 2022)
Online fitness coaches help people achieve a healthy lifestyle by offering customized solutions. The demand for professional coaching is expected to grow in the coming years. Nevertheless, no applications in the market address the problems in the coaching process. Today, coaches and clients had to use many third-party apps. The reason for this is that no single fitness coaching app offers communication and exercise-tracking features. Even though some apps meet some of these requirements, they are out of reach for most people's budgets. This paper aims to suggest a robust and full-fledged app to mitigate those issues. FitFlame is the name of the proposed app. Both coaches and clients can benefit from this app. Also, FitFlame is a fitness coaching system available on mobile and the web. It helps clients locate and contact coaches, subscribe to coaching plans, and track their progress. It does away with third-party programs and gives users a better experience.